1
Chat with our AI personalities
First you distribute: x2-9 = (x-3)(x+3) and that is you numerator. Distribute x2-6x+9. Find two #'s that mult. to make 9 and add to make 6. 3x3=9 and 3+3=6. now you replace the 6x with -3x and -3x so rewrite the problem as x2-3x-3x+9 then you distribute x(x-3)-3(x-3) so x2-6x+9 becomes (x-3)(x-3) and that is your denominator. Tharefore: (x-3)(x+3) over (x-3)(x-3) then cross out like terms and your answer is (x+3) over (x-3)
X2+3x+x+3=x(x+1)+3(x+1)=(x+3)(x+1)
(x2+10x+21)/(x+3) = (x+7)
(x2 + 2x + 15)/(x - 3) = x + 5 + 30/(x - 3) where x ≠3
x2 + 4x - 9 = 5x + 3 ∴ x2 - x - 12 = 0 ∴ (x + 3)(x - 4) = 0 ∴ x ∈ {-3, 4}